THE MAIN FEARS OF LEARNING AN ORIENTAL LANGUAGE AND WAYS TO OVERCOME THEM - Saidnazarova Nodira Otakhon qizi (Western European Studies, 2024)
In this article, we explore the main fears that students may have when learning Oriental languages and discuss effective strategies to overcome these fears. By facing these fears and implementing practical solutions, students can learn the complexities of Oriental languages with confidence and determination.
Keywords: oriental languages; fears; grammar